Profile of hepatocellular carcinoma in the Republic of Moldova: first-hand information on the presentation, distribution and etiologies - Turcanu Adela; Pitel Ecaterina; Dumbrava Vlada-Tatiana; Tcaciuc Eugen; Donscaia Ana; Peltec Angela; Pineau Pascal (Sciendo, 2019)
Introduction. Moldova is the European country with the highest incidence of hepatocellular carcinoma (HCC) in both sexes. There is, however, no data comprehensively describing the presentation and the risk factors of HCC in the country. We decided to analyze cases of HCC recently received in a tertiary healthcare Institution from Chisinau, the Moldovian capital.